Achondroplasia - How do I manage this? A case report and review of the literature (Indian Journal of Case Reports, 2026)
Achondroplasia, while being the most common form of disproportionate short stature, is a relatively rare case to encounter during anesthetic practice. With various problems, such as bony anomalies of the vertebral spine and difficult airway, planning anesthetic management of these patients requires special considerations. We report the case of a 54-year-old female with Achondroplasia, with fracture of the neck of the right femur treated by open reduction and internal fixation of the fracture. An appropriate sensory level could not be achieved on administration of spinal anesthesia despite an adequate dosage of Bupivacaine. Subsequently, conversion to general anesthesia was required. Surgery was uneventful, and the patient was discharged from the hospital after 48 h.